Protective potentials of polymyxin B and honey against bacterial lipopolysaccharideinduced endotoxemia in mice - Mithun, Ferdous Hasan; Bhuiyan, Md Eftakhar Jahan; Hossain, Md Golzar; Debnath, Chirojit; Nazir, K H M Nazmul Hussain; Akter, Sharmin (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The experiment aimed to determine the effects of lipopolysaccharide (LPS), polymyxin B, and honey on survival rates, hematological parameters, liver and kidney biomarkers, blood glucose levels, serum insulin levels, and histopathology of the liver, kidney, lungs, brain, and pancreas in LPS-challenged mice. Materials and Methods: 50 male Swiss Albino mice (Mus musculus), aged 3 weeks, were randomly assigned into 5 groups (10 mice per group): Control group (A), LPS (2 mg/kg bwt/day IP in NS) treated group (B), polymyxin B (1.2 mg/kg bwt/day IM) pre-treated plus LPS (2 mg/kg bwt/ day IP in NS) treated group (C), honey (10 gm/kg bwt/day PO) pre-treated plus LPS (2 mg/kg bwt/ day IP in NS) treated group (D), both polymyxin B (1.2 mg/kg bwt/day IM) and honey (10 gm/ kg bwt/day PO) pre-treated plus LPS (2 mg/kg bwt/day IP in NS) treated group (E). The LPS was administered intraperitoneally (IP) at 80 μg/mice/day, diluting in normal saline. After 16 weeks, the mice were sacrificed, and blood samples and organs (liver, kidney, lung, brain, and pancreas) were collected for laboratory tests. Results: The results revealed that in LPS-treated mice, the mortality rate was the highest, and hemato-biochemical parameters were altered. Histopathological examination in the group treated with LPS showed disarrangement of hepatocytes, cellular infiltrations in the glomerulus, alveolar congestion in the lungs, several nerve fiber degenerations in the brain, and degenerative changes in pancreatic islets. The mortality rate and hemato-biochemical and histopathological changes were restored by the combined treatment of polymyxin B and honey. Conclusion: LPS has detrimental effects on survival rate and hemato-biochemistry, which are lessened by taking honey and polymyxin B supplements. Adv. Vet. Anim. Res., 11(2): 503-515, June 2024 http://doi.org/10.5455/javar.2024.k800